RAILWAY MODERNIZATION IN INDONESIA: A COMPARATIVE STUDY OF FOUR COUNTRIES AND ITS POLICY IMPLICATIONS - Dimas Pasurangga; Sora Baltasar (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines structural and spatial gaps in Indonesia’s railway network through a comparative analysis with Japan, India, the Philippines, and Uzbekistan, aiming to formulate adaptive, efficient, and sustainable railway modernization strategies. Using a qualitative descriptive-comparative approach grounded in pragmatism, the research emphasizes the policy relevance of global best practices adapted to Indonesia’s context. Lessons from Japan and India highlight network integration, business diversification, and logistics efficiency, while the Philippines and Uzbekistan demonstrate the importance of adaptive governance, technological innovation, and institutional reform in strengthening interregional connectivity. In Indonesia, modernization should integrate the roles of PT Kereta Api Indonesia (KAI), the Directorate General of Railways, and local governments to enhance connectivity, improve logistics efficiency, and promote equitable regional development. These findings provide a conceptual and managerial reference for designing inclusive, adaptive, and equitable national public transport policies.